Surface modification using EDM wire cut method: a feasibility study - Choo, Chee Hua (2016)
Wire electrical discharge machining wire EDM removes electrical conductive materials by the electrical sparks. This research is focused on the surface integrity and the process parameters of the selected materials eg. steel and A-alloy. It is expected that grain refinement occurred due to rapid solidification of molten metal on the surface. So, hardness of material can be increase. Recast layer formed on the metal surface by wire EDM is expected to be harder than the subsurface, due to the rapid-cooling of the molten metal. Present work attempts to identify the effect of various EDM parameters on the layer formation. A preliminary metallurgical investigation of EDM machined surface was conducted to determine the effect of process parameters like wire speed and spindle feed rate to morphology and microstructure change of work piece.